Agile Development of a Mobile Application for Remote Monitoring of Neurological Patients - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This research aims to address the issues of limited accessibility and efficiency in monitoring neurological patients by developing an Agile Development-based Remote Monitoring application. The development method includes identifying user needs through interviews and questionnaires, designing initial prototypes using Adobe XD, piloting testing with target users, and evaluating users using the System Usability Scale (SUS) and in-depth interviews. This research indicates that the application successfully enhances treatment accessibility, user satisfaction, and the effectiveness of neurological patient monitoring. The primary contribution of this research lies in providing user-oriented technological solutions in health monitoring, with the potential for further development to enhance overall remote healthcare service quality.